War in the air, 1914-45 - Murray, Williamson (London : Cassell, 1999)
Explores how airplanes were used in World War I and World War II.
The First World War -- The interwar years -- The air war in Europe -- Air war in the Pacific.
Includes bibliographical references (pages 216-217) and index.
Keywords: 1900-1999; World War, 1914-1918 -- Aerial operations; World War, 1939-1945 -- Aerial operations; Air warfare -- History -- 20th century; History